Enhancing implant surfaces: mechanical stability and cytocompatibility of DNase I coatings deposited by alternating current electrophoretic deposition - Aktan, Merve Kübra; Zayed, Naiera; Yadigarli, Aydan; Killian, Manuela Sonja; Lavigne, Rob; Teughels, Wim; Braem, Annabel (Frontiers in Bioengineering and Biotechnology, 2026)
Deoxyribonuclease I (DNase I) is an enzyme that hydrolyzes the phosphodiester bonds in the DNA backbone, enabling efficient DNA degradation. This activity is particularly relevant for degrading extracellular DNA (eDNA), a key structural component of the biofilm extracellular matrix that enhances bacterial attachment to implant surfaces and promotes cell-to-cell adhesion. By disrupting this matrix, DNase I offers significant potential to indirectly inhibit biofilm formation and reduce the risk of implant-associated infections (IAIs). In previous work, we developed a rapid electric field-assisted technique for producing anti-infective DNase I coatings on titanium (Ti) implant surfaces. To further evaluate clinical applicability, this study investigates the mechanical stability and in vitro cell compatibility of DNase I coatings applied to polydopamine (PDA)-functionalized Ti. Coatings were mechanically stressed using ultrasonication, followed by characterization of surface wettability and chemical composition. Compared to traditional dip-coating, AC-EPD-generated DNase I coatings exhibited greater stability, maintaining consistent wettability after 2 h of ultrasonication. Surface chemistry was examined using time-of-flight secondary ion mass spectrometry (ToF-SIMS), which detected amino acid fragments on both coating types. Notably, AC-EPD coatings contained a higher disulfide bond content, suggesting enhanced structural integrity. Furthermore, given the relevance to dental implant applications, human oral keratinocytes (HOKs) were used to assess cytotoxicity, cell adhesion, and spreading. The results indicated no cytotoxic effects, while promoting improved cell adhesion at both 24-h and 48-h incubation periods. Overall, these findings demonstrate that AC-EPD DNase I coatings are mechanically robust and biocompatible, making them a promising strategy for preventing implant-associated infections (IAIs) in dental implant applications.